Pengembangan Metode Evaluasi Komitmen Ketahanan Pangan Dan Gizi Pemerintah Daerah Provinsi Di Indonesia - Novfitri Syuryadi; Drajat Martianto; Dadang Sukandar (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: Methods of evaluation of the regional government’s commitment in the development of food and nutrition security are not yet available. The index that measures the government’s commitment to national food and nutrition security is HANCI. Therefore, this study aimed to develop a method of evaluating the commitment of the regional government in the development of food and nutrition security.Objectives: This study aimed to develop a method of evaluating the commitment of regional government in the development of food and nutrition security. Methods: The design of this study was a cross-sectional study using secondary data that refers to HANCI measurements. This research stage consisted of identification of potential indicators, qualitative selection of candidate indicator, assessment of indicator used the scoring method, and applied the method to provinces in Indonesia. Results: The result showed shortlist of 42 commitment indicators of food and nutrition security and aggregate score of provinces. Only 2.9% of provinces had high commitment and 17.6% of provinces with low commitment level. Highest rank was achieved by East Java Province and the lowest rank was East Nusa Tenggara Province. Low political commitment could lead to low priority of food and nutrition interventions. The government was in need to make regulations/policies and prepare adequate budgets for specific and sensitive food and nutrition programs.Conclusions: Development of this evaluation method is relevant to show the commitment of the regional government. The government needs to improve efforts to address problems of food and nutrition.ABSTRAK Latar Belakang: Metode evaluasi komitmen pemerintah daerah provinsi dalam pembangunan ketahanan pangan dan gizi saat ini belum tersedia. Index yang mengukur komitmen pemerintah terhadap ketahanan pangan dan gizi secara nasional adalah HANCI. Oleh karena itu, studi ini bertujuan untuk mengembangkan metode evaluasi komitmen pemerintah daerah provinsi dalam pembangunan ketahanan pangan dan gizi.Tujuan: Penelitian ini bertujuan untuk mengembangkan metode evaluasi komitmen pemerintah daerah provinsi dalam pengembangan ketahanan pangan dan gizi.Metode: Desain penelitian ini adalah cross-sectional study dengan menggunakan data sekunder yang mengacu pada pengukuran HANCI. Tahap penelitian terdiri dari identifikasi indikator potensial, seleksi calon indikator secara kualitatif, perhitungan skor menggunakan metode scoring, dan aplikasi metode pada provinsi di Indonesia.Hasil: Hasil menunjukkan shortlist 42 indikator komitmen ketahanan pangan dan gizi dan skor agregat provinsi. Berdasarkan hasil penelitian diketahui bahwa hanya 2,9% provinsi yang memiliki komitmen tinggi dan 17,6% provinsi memiliki tingkat komitmen rendah. Provinsi Jawa Timur berada pada peringkat pertama sedangkan peringkat terakhir ditempati oleh Provinsi Nusa Tenggara Timur. Komitmen politik yang rendah dapat menyebabkan rendahnya prioritas intervensi pangan dan gizi. Pemerintah perlu membuat peraturan/kebijakan dan menyiapkan anggaran yang memadai untuk program pangan dan gizi secara spesifik maupun sensitif.Kesimpulan: Pengembangan metode telah relevan digunakan untuk melihat komitmen pemerintah daerah provinsi. Pemerintah perlu meningkatkan upaya berupa pembuatan peraturan dan kebijakan serta anggaran untuk penanganan masalah pangan dan gizi.